دور القيادة الأدارية الأبداعية في تطوير أداء عينة من الأداريين ورضاهم الوظيفي ببعض مديريات التربية والتعليم بسلطنة عمان - Al-Musalami Fatema Saqer Juma (Universiti Sains Islam Malaysia, 2024)
The current study investigates the variations in the educational and the administrative roles that the leader performs in the educational institutions in order to improve employees' performance. Therefore, the study aims to determine the main factors that influence employees' performance and job satisfaction and measures whether there is a relationship between creative managerial leadership practices and employees' performance and job satisfaction. Furthermore, it aims to highlight the importance of creative managerial leadership practices and employees' performance and job satisfaction and recommends way to activate this role. In order to fulfil the aims of the study, a mixed method approach was utilized with the use of two surveys which were administered to a random sample of 382 participants. In addition, unstructured interview was used with 12 leaders and employees in government educational institutions in the Sultanate of Oman. The results of the study indicate that there is a positive correlation between the creative managerial leadership practices of leaders and their employees' performance and job satisfaction. They also show that there is an average impact for job type on employees' performance and job satisfaction in favour of the leaders. The results also indicated that there is a weak impact of educational region in favour of Bureimi Governorate. A number of recommendations were suggested in order to activate the role of creative managerial leadership practices in improving employees' performance and their job satisfaction.